2021
DOI: 10.1016/j.vaccine.2021.06.038
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccination rates vary by community vulnerability: A county-level analysis

Abstract: We used the COVID-19 Community Vulnerability Index and 7 theme scores to assess associations between vulnerability and county-level COVID-19 vaccination (n = 2415 counties) through May 25th, 2021. When comparing vaccination rates among quintiles of CCVI scores, Theme 3 (housing type, transportation, household composition, and disability) was associated with the largest disparity, with the least vulnerable counties (Q1) having 33% higher rates of vaccination among individuals aged 18+ (53.5% vs 40.2%) compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
54
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 10 publications
11
54
0
2
Order By: Relevance
“…Consistent with other studies, we found a strong association between socioeconomic vulnerability and low vaccination rates that has persisted since our data collection. 2 , 3 , 13 While counties with higher SES vulnerability had more vaccine sites per capita, this increased site density did not mitigate the association of SES with lower vaccination rates. Persistent vaccination inequities may have reflected non-residents using the sites and limited vaccine supply, as well as other access challenges related to lack of transportation and inflexible time-off policies for working class employees.…”
Section: Discussionmentioning
confidence: 95%
“…Consistent with other studies, we found a strong association between socioeconomic vulnerability and low vaccination rates that has persisted since our data collection. 2 , 3 , 13 While counties with higher SES vulnerability had more vaccine sites per capita, this increased site density did not mitigate the association of SES with lower vaccination rates. Persistent vaccination inequities may have reflected non-residents using the sites and limited vaccine supply, as well as other access challenges related to lack of transportation and inflexible time-off policies for working class employees.…”
Section: Discussionmentioning
confidence: 95%
“…Prior studies in the United States [ 14 ] and Israel [ 16 ] have found that socioeconomic vulnerability is linked with lower vaccination rates; however, these studies focus on the concept of a socioeconomic vulnerability index more broadly, rather than on individual socioeconomic factors. Another recent US-based study found that vaccination rates are strongly correlated with housing problems [ 14 , 23 ]; however, this analysis did not consider COVID-19 incidence rates as an additional outcome measure. Furthermore, this current study is novel because it includes a large number of socioeconomic factors in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the low vaccination rates in these counties, poor compliance to public health measures, hospital closures, increased likelihood of unemployment, and delay in seeking care due to lack of insurance. [ 45 , 46 ] This reiterates the need for public health outreach and the development of programs and policies to address the disparity.…”
Section: Discussionmentioning
confidence: 99%